Effectiveness and Safety of Acupoint Catgut Embedding for the Treatment of Poststroke Constipation: A Systematic Review and Meta-Analysis. (5th July 2022) - Guo, Mao; Le, Xie; Qin-yu, Wang; Ye, Mao; Sheng-qiang, Zhou; Yao, Xie; Da-hua, Wu; Bai-yan, Liu
Abstract : Objectives . Acupoint catgut embedding therapy has shown effectiveness in treating functional constipation; however, relevant, high-quality clinical evidence is scarce. This study aimed to systematically assess the effectiveness and safety of acupoint catgut embedding in treating poststroke constipation. Methods . Correlative randomized controlled trials were identified through a comprehensive literature search of PubMed, Cochrane Library/Cochrane Central Register of Controlled Trials, Web of Science, Embase, China National Knowledge Internet, Chinese Biomedical Literature Database, Wanfang, and VIP databases from inception until February 2022. Meta-analysis was performed using RevMan 5.3 software. Results . Fifteen trials involving 1084 patients were identified. The meta-analysis revealed that the acupoint catgut embedding group was significantly superior to the non-catgut embedding group with regard to the efficacy rate (RR = 1.27, 95% CI (1.19, 1.37), P < 0.05 ), the first defecation time (MD = −3.08, 95% CI (−4.53, −1.63), P < 0.05 ), the defecation sensation score (MD = −0.44, 95% CI (−0.61, −0.26), P < 0.05 ), the degree of difficulty in defecation (MD = −0.73, 95% CI (−1.10, −0.37), P < 0.05 ), the PAC-QOL scale score (MD = −10.06, 95% CI (−13.47, −6.64), P < 0.05 ), and the symptom integral (MD = −3.15, 95% CI (−3.60, −2.71), P < 0.05 ). However, there was no significant difference in the stool property score (MD = 0.06, 95% CI (−0.39, 0.50), P > 0.05 ) as well as the incidence of adverse reactions (RD = 0.01, 95% CI (−0.01, 0.03), P > 0.05 ) between the two groups. Conclusions . The results showed that acupoint catgut embedding is probably an effective and safe acupuncture treatment strategy for poststroke constipation. Nevertheless, more rigorously designed, standardized, large-sample, and multicenter randomized controlled designs are warranted to further verify the findings of this study.